Aerodynamic Study Of Wingtip-Mounted Propeller And Distributed Propulsion System - Qiao, G.; Barakos, G.N. (My University, 2024)
Today, most innovative vehicle designs, such as those with distributed propulsion (DP) systems, are equipped with multiple rotors and propellers. DP systems create complex interactional aerodynamics, which remain largely unexplored and not fully understood. This paper presents a high-fidelity aerodynamic analysis of a tip-mounted propeller (TMP) combined with an over-the-wing (OTW)-installed system. Four configurations were tested using fully resolved simulations with the HMB3 CFD solver. The results indicate that the interactional effects in all configurations influence the propeller and wing performance. Notably, the proposed configuration featuring both TMP and DP produced 3.5% more thrust compared to the configuration with TMP-only, while also enhancing efficiency. This improved wing performance, yielding more lift, less drag and resulted in higher lift-to-drag ratio (L/D). These benefits were due to the thrust distribution and propeller slipstream. Additionally, the OTW-DP system resulting in higher pitching moments, suggesting that the entire vehicle should be considered to achieve the overall objective of high efficiency.